A solução de problemas como potência prática na performance dos jogos teatrais: de John Dewey à Viola Spolin - Vieira, Karine Ramaldes (2020)
This study seeks to understand how the process of problems-solving, from the perspective pointed out by John Dewey (1859-1952), constitutes the master structure of the approach and development of the theater games proposed by Viola Spolin (1906-1994). It investigates the path that John Dewey's studies have taken in the elaboration of the problem-solving process, in order to arrive at the games systematized by Viola Spolin. This question becomes fundamental not only for the studies relating to Spolin's theater plays, but also for theater teaching and performance studies in Brazil. It tries to examine some questions that pervade the construction of the experience in the theater games of Viola Spolin from the process of problems-solving. This is an approach, which elaborates mental, psychological, practical, contextual analysis, interpretation, and analyzes how these can enrich the studies concerning the pedagogy of theatrical practice in a more comprehensive way.